Ethnic identity, social mobility and the role of soulmates (2018)
My background in Physics and my career start as a Management Consultant often raises eyebrows. The knowledge that one of my early (and strong!) drivers was to prove myself as a woman often softens this surprise and explains the switch to Gender Studies. It then comes as no surprise that I am driven by the question of what it is like to belong to a minority group. (Or, as I would phrase it after writing an academic book: I am intrigued by what it is like to be seen as a member of what is considered to be a minority category.) Remarkably enough, this interest was not inspired primarily by my ethnic background. It was not until I learned about the formal Dutch categorization system in one of my Social Science classes that I realized I was formally an ‘allochtoon’ (foreigner). Until then, the fact that my father and grandparents were from Indonesia did not mean more to me than my grandma’s lovely spring rolls and the water bottle typically found next to the toilet. It still doesn’t. I suppose that something as ‘superficial’ as my Dutch name has been an important reason that I never questioned whether I belonged in the Netherlands. This contrasts with many others, whose ethnic backgrounds have a large impact on their sense of belonging. I find this an intriguing observation.